IDEOLOGY AND PARTY ACTIVITY FROM THE PERSPECTIVE OF LITHUANIAN PARTY LEADERS - Butkevičienė, Eglė; Vaidelytė, Eglė; Žvaliauskas, Giedrius (Politologija, 2015)
The article deals with the analysis of the reasons why ideology is not important part of party activities. Even if the labels with some shades of ideology are being used nevertheless parties do not have clear ideological position and prefer pragmatism. Post-communist politics presents wide range of latent cleavages and creates unique opportunity for development and formation of politics based on of the differences of social and cultural level. Nevertheless in Lithuanian political map we can notice just one type of cleavage, i.e. Communist – Anti-Communist cleavage. In 1990 Lithuania has started its way towards both democracy and market capitalism. The transformation of centrally planned-administrative economic system to market economy fostered social and economical changes in Lithuania. Surprisingly these transformations has no significant impact on formation “Western” Left—Right cleavage with dominant socio-economic content. The non-ideological position of Lithuanian parties manifests the situation as if all Lithuanian population has the same economic preferences and as if Lithuania has no significant socio-economic problems that could be the core issue for confrontation among different Lithuanian parties. The article first evaluates the level of internal democracy of Lithuanian parties and reveals that opportunities of party members to participate in decision making process are not sufficient. Value conflicts among parties highly depend on the political will of party leaders. This article focused on the analysis of 9 interviews with the party leaders or the deputy chairmen from the 9 main Lithuanian parties. The aim of the interviews was to discuss the role of ideology in party politics and activities. The study revealed that the lack of ideology identity among Lithuanian parties cannot be explained by the freshness of Lithuania party system that actually is almost 20 years old, or by political immaturity of Lithuanians. It is a problem of system, as even the highest authorities of the parties demonstrate the lack of ideological thinking in explaining certain political party issues. Nevertheless party authorities know main value ‘labels’ of their political ideologies, party leaders themselves admitted that ideological declaration is one thing and real political activity is another one. Summarizing, it might be noticed, that ideology is important for party leaders as theoretical construction, but in party decision making or at the highest political level in Seimas and Government the party ideological values are ignored. Interviews with the authorities of main political parties in Lithuania were conducted in 2007. The results of the interviews don’t promise the long term political cleavages that could make the political life in Lithuania normal in nearest future. Though the authorities of Lithuanian parties have institutional possibilities to control party organization, however, they are not a power that may put Lithuanian parties in a clear ideological framework and foster coherence between parties and society. The main obstacle for the emergence of political cleavage in Lithuania is not a Lithuanian social mentality that is not ready to think ideologically and vote according to it, but Lithuania political parties unwilling to respond to the different interests of Lithuanian society.